Basidiome formation of an edible wild, putatively ectomycorrhizal fungus, Phlebopus portentosus without host plant - Jaturong Kumla (2018)
Phlebopus portentosus is a popular wild edible ectomycorrhizal fungus in northern Thailand. In general ectomycorrhizal fungi produce basidiomes when associated with a host plant. In this paper mycelium growth and basidiome production of P. portentosus were examined in pure culture both in vitro and in pot-culture experiments. Five mycelial strains of P. portentosus were isolated from basidiomes and used in the experiments. The mycelia grew fastest on sorghum grains supplemented with fungal-host solution. The mycelia produced sclerotia-like structures after 3 wk incubation in darkness at 30 C. All strains of P. portentosus had the ability to form primordia. The primordia were formed under lowered temperature, high humidity and a 12 h photoperiod. They developed to mature basidiomes after 8-12 d in in vitro. In the pot-culture primordia were found after 28-35 d incubation in the greenhouse and mature basidiomes released basidiospores within 6-8 d. Basidiospores were germinated on fungal-host medium and formed mycelial colonies. This fungus showed an ability to produce basidiomes even 2 y after the original isolation from tissues. This research provides valuable information concerning the techniques and protocols for the large scale commercial production of P. portentosus basidiomes in the absence of a host plant. © 2012 by The Mycological Society of America.